Cost minimisation technique in geo-distributed data centres - Khalaf, Ayesheh Ahrari; Hassan Abdalla Hashim, Aisha (Inderscience Enterprises Ltd., 2019)
Significant growth of Big Data leads to a great opportunity for data analysis. Data centres are continuously becoming more popular. At the same time data centres’ cost are increasing as the amount of data is growing. Simply as Big Data is significantly increasing, data centres are facing new challenges. Hence the idea of geo-distributed data centre is introduced. This project investigates on the main challenges that data centres face and presents an enhanced technique for cost optimisation in geographical distributed data centres. Parameters involved such as task assignment, task placement, big data processing and quality of service are analysed. Analytical evaluation results show that joint parameters technique proposed outperformed separate parameter techniques in some cases even with 20% enhancement. Academic Gurobi solver is used for the evaluation.